(untitled) (Research, Society and Development, 2023)
The university student’s routine is marked by many demands, from difficulties to emotional illness. Given this scenario, this work aims to conduct a survey on the main contributions of socio-emotional skills training programs for mental health. The method used in this study was exploratory bibliographical research that aimed to build a narrative review. For this purpose, searches were carried out for articles, theses, and dissertations indexed in the following electronic databases available online: Scientific Electronic Library Online (SciELO); Latin American and Caribbean Literature in Health Sciences (Lilacs), and Google Scholar. The following categories of descriptors were used for the research: “treinamento de habilidades socioemocionais”; “socio-emotional skills training” and “socio-emotional skills training”. All these terms were associated with the descriptor “mental health” in Portuguese, English, and Spanish. As for the results, 8 studies were found and analyzed that presented contributions of training programs for socio-emotional skills in the mental health of different sociodemographic groups. It is concluded that the use of socio-emotional skills training programs for university students can be an efficient alternative that can be adopted by higher education institutions as a way of promoting the mental health of their students and preventing illness.